2006
DOI: 10.1159/000097858
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Sphenoidal Aspergillosis: Successful Treatment with Sphenoidotomy and Voriconazole

Abstract: Treatment of invasive sphenoidal aspergillosis is surgical, followed by antifungal therapy, mostly amphotericin B. To optimize the adjuvant antifungal treatment, which is often limited by severe side effects, the new triazole antifungal agent voriconazole with broad coverage of fungal pathogens including Aspergillus was investigated in a study of 4 patients with clinical, radiological and histological signs of invasive sphenoidal aspergillosis. They first underwent endoscopic sphenoidotomy with drainage and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 34 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…Despite the extremely poor outcome of acute fulminant invasive fungal sphenoiditis, the treatment outcome of chronic invasive fungal sphenoiditis in our study (survival rate of 75%) was comparable with other studies reporting survival rates of 60% and 100% with limitations such as case reports and short follow-up period [8,11]. Fatal mycotic aneurysmal rupture occurred in two patients.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Despite the extremely poor outcome of acute fulminant invasive fungal sphenoiditis, the treatment outcome of chronic invasive fungal sphenoiditis in our study (survival rate of 75%) was comparable with other studies reporting survival rates of 60% and 100% with limitations such as case reports and short follow-up period [8,11]. Fatal mycotic aneurysmal rupture occurred in two patients.…”
Section: Discussionsupporting
confidence: 74%
“…The typical symptoms of IFS of the sphenoid sinus are prolonged diffuse headache and rhinorrhea, followed by sudden visual disturbance or ocular motion impairment resulting from orbital apex syndrome or cavernous sinus syndrome [11]. In our study, the most common associated symptoms and signs were visual disturbance and headache.…”
Section: Discussionmentioning
confidence: 56%
“…A treatment of 6 to 12 months is being advocated in skull base aspergillosis these days. 16,17 There were significantly increased number of adverse nephrotoxic and cardiotoxic events in patients on amphotericin as compared to voriconazole in this series. Though 3 patients developed skin rashes on voriconazole, they were transient and did not hamper the administration of voriconazole to the patients and disappeared after the stopping of the drug.…”
Section: Discussionmentioning
confidence: 67%
“…15 The optimum duration of antifungal drug administration for chronic invasive fungal sinusitis is controversial and reports vary widely, depending on the severity of the disease and institution from 2 months to more than 15 months. [16][17][18] In a review by Webb and Vikram on chronic invasive sinus aspergillosis in immunocompetent hosts, they found that treatment failure and mortality were not associated with degree of surgical intervention. But patients receiving azoles with activity against aspergillosis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…17 The optimum duration of antifungal drug administration for chronic invasive fungal sinusitis is controversial and reports very widely depending on the severity of the disease and institution from 2 months to more than 15 months. [49][50][51] In a review by Webb and Vikram on chronic invasive sinus aspergillosis in immunocompetent hosts, they found that treatment failure and mortality were not associated with degree of surgical intervention. But patients receiving azoles with activity against aspergillosis (i.e.…”
Section: Aijcrmentioning
confidence: 99%